Risk Factors of Malnutrition among Under Five Children Admitted in a Nutritional Rehabilitation Center in Lalitpur - Sharma, Pratima; Onta, Mandira (Journal of Nursing Education of Nepal, 2023)
Malnutrition not only posses immediate threat to child’s health and life but also entails long term impact to physical and mental growth. Study Entitled “Risk Factors of Malnutrition among Under Five Children Admitted in a Nutritional Rehabilitation Center in Lalitpur” was conducted to assess the risk factors of malnutrition among under 5 children using case control design. Cases included malnourished under five children admitted in Nutritional Rehabilitation Center (NRC) Lalitpur and controls included well nourished under five children attending Well Baby Clinic of Tribhuvan University, Teaching Hospital (TUTH), Maharajgunj in the ratio of 1:2. Altogether 136 samples were selected by non-probability purposive sampling technique. Interview schedule with semi-structured questionnaire was used for data collection. The findings were analyzed using descriptive statistic (mean, standard deviation) and inferential statistics (multiple logistic regression) for identifying the strength of association. Findings of the study shows that ethnicity (Adjusted Odds Ratio [AOR]=2.462), birth weight (AOR=7.683), birth order (AOR=5.906), number of family members (AOR=2.8), father’s occupation (AOR=6.539), economic status (AOR=2.927), Vitamin A (AOR=11.592), washing hand by mother before feeding the child (AOR=40.422), frequency of feeding the child (AOR=24.178), use of purified drinking water (AOR=5.040), method of waste disposal (AOR=16.892), other illness (AOR=5.38), place of first health seeking (AOR=17.435) and previous hospitalization (AOR=2.273) were significantly associated with malnutrition. Most of these risk factors if identified timely can be prevented and controlled by appropriate intervention.